A Poet in Austyn’s Pocket: A Fantastical Tale for Mothers Who Think They’ve Lost Their Play - Burrow, Lauren E. (Journal of the Motherhood Initiative for Research and Community Involvement, 2025)
In dedication to my children ... this is a bedtime story I always meant to write for y’all. This short, multichapter fairy tale is a fantastic(al), semi-autobiographical tale of a MotherScholar battling self-doubt, work demons, and a lack of creativity in the United States during the early quarantine months of the global COVID-19 pandemic. “MotherScholar” is a unique and intentional stylization of “motherscholar” (a term originally coined by Cheryl Matias, a Pinay antiracist scholar) that emphasizes, through intentional capitalization, the importance of my two identities while maintaining the original lack of spacing to signal a blended coexistence shifting towards a singular identity (Burrow and Jeffery). This fairy tale was structured in the vein of similar “social fictions” (Bhattacharya; Leavy) that are written in literary form to both entertain and educate while offering both social critique and “critical hope” (Bishundat et al.). At its heart, this is a bedtime story written to my children as I confess the tragic journey of fighting to rediscover my hope in a fairytale world of childhood poetry, song, and story as my scholarly labour was under attack and being belittled by the “work harpies.” Universally, the fairy tale should speak to those MotherScholars and mothers whose gentle and joyful scholarship and labours are often discounted and dismissed because they take creative, playful forms.